Edaravone promotes activation of resident cardiac stem cells by transplanted mesenchymal stem cells in a rat myocardial infarction model - Zhang, Guang-Wei; Gu, Tian-Xiang; Sun, Xue-Jun; Wang, Chunyue; Qi, Xun; Wang, Xiao-Bing; Li-Ling, Jesse (The Journal of thoracic and cardiovascular surgery, 2016)
To explore the effect of edaravone on bone marrow mesenchymal stem cells (BMSCs) transplanted to treat acute myocardial infarction (AMI) and the underlying mechanism. After pretreatment or treatment with edaravone under conditions of deep hypoxia and serum deprivation, the rat BMSCs were evaluated for reactive oxygen species (ROS), Akt pathway, apoptosis, migration, and paracrine function mediating cardiac stem cell (CSC) activation. Edaravone-pretreated BMSCs, control-released edaravone, and BMSCs were respectively transplanted into a rat AMI model. Apoptosis and paracrine functions of the BMSCs, resident CSC activation, and myocardial regeneration and function were measured at various time points. Compared with the control and edaravone pretreatment, edaravone treatment showed significantly increased apoptosis inhibition, migration, and cytokine secretion of BMSCs under an in vitro deep hypoxia and serum deprivation condition (P < .05), via inhibiting intracellular accumulation of ROS and prolonging the Akt pathway activation. At 24 hours postoperatively, up-regulated expression of cytokines within the transplanted area, and decreased apoptotic BMSCs, were detected in the BMSC + edaravone group, compared with the BMSCs and edaravone pretreatment BMSC groups (n = 10 for each group, P < .05). Four weeks later, the BMSCs + edaravone group showed more CSCs, CSC-derived cardiomyocytes, new vessels, and myocardial density within the ischemic area, and improved ejection fraction, compared with the other groups (n = 10 in each group, P < .05). Edaravone can protect the BMSCs against hypoxia and activate their potential to activate CSCs via the Akt pathway. The combined treatment can promote angiogenesis, resident CSC-mediated myocardial regeneration, and cardiac function after AMI, providing a new strategy for cell therapy.